El museo efímero del olvido en la Universidad Nacional de Colombia - García Maidana, María Soledad; Lleras Figueroa, Cristina (Universidad Nacional de Colombia, 2019)
The curatorship and the assembly of the exhibition: The Ephemeral Museum of Oblivion, made on the campus of the National University of Colombia in 2015, allowed the authors to reflect on the nature of the work of art, its temporary and ephemeral nature, and its relationship with the museum. This publication is perhaps the last insistence of the ephemeral museum that, like a ghostly apparition, does not cease to travel the path between memory and oblivion. The Museo efímero del olvidoʺ appeared for the first time in 2014 as a curatorial research project that covered a group of expectations and uncertain concepts about art, memory, museum and the region. This project was the winner of the 15th Salón Regional de Artistas Zona Centro (for Cundinamarca, Boyacá and Bogotá) in 2015. The objective of this project was to put into dialogue the different agents of the regional artistic field to mobilize reflection on the institutionalization of memory and the marginality of oblivion within the monolithic figure the 'Museum'.ʺ (HKB Translation) --Page 15